The production of agricultural space: conflict threads between peasantry and agribusiness - Santos de Lima, Wylamys; Oliveira Silva, Patrick (Seven Editora, 2023)
The field has been undergoing significant changes in the way of producing, in the techniques applied, and in the relations of production deriving, mainly, from the agricultural and agrarian policies implemented by the actions of the State, articulated with the interests of capital in multiple scales. In this sense, this research seeks to analyze the processes engendered by the metabolism of capital about the production and reproduction of agrarian space through the threads leading to the conflict between agribusiness and peasantry, having as spatial cut the municipalities of Simão Dias and Poço Verde in Sergipe and Coruripe in Alagoas. The methodological procedures used in this work are the bibliographical research, mainly of texts of the discipline of Agrarian Theory taught in the Graduate Program in Geography – PPGEO, of the Federal University of Sergipe, and readings in the research group. The research was based on a Historical-Dialectical Materialist reading of the conflict between the logic of peasant production and the logic of agribusiness production, inscribed in the interaction between capital and labor. The advance of agribusiness restricts family peasant production with the establishment of monoculture as the only possible planting model and uses the logic of capitalist agriculture to submit peasant production to the market, at the same time, which makes work in the field precarious. In the case of Sergipe, the main conflict materializes through the submission of peasant income. And, in the case of Alagoas, the appropriation of the precariousness of work with the intensification of flywheel work.DOI:https://doi.org/10.56238/alookdevelopv1-003